Growth in Volume of Euglena gracilis During the Division Cycle - Kempner, E. S. (1970)
The distribution of volumes of Euglena gracilis cells was measured conductimetrically. The volume spectrum of cultures in balanced growth was analyzed by the method of Collins and Richmond. The kinetics of volume increase of Euglena is neither linear nor exponential; the growth rate of small and large cells is low, but intermediate size cells show the largest growth rate.